2020
DOI: 10.3390/su12020737
|View full text |Cite
|
Sign up to set email alerts
|

Becoming Carbon Neutral in Costa Rica to Be More Sustainable: An AHP Approach

Abstract: We propose addressing an organization’s adoption of an environmental certification as a multicriteria problem considering environmental sustainability as well as economic and strategic aspects. Our methodological approach uses the Analytical Hierarchy Process (AHP), which we use in an empirical application to analyze the adoption decision of several Costa Rican firms and institutions. Firstly, we select a set of economic, strategic, and environmental criteria that seem relevant for the organization’s direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…erefore, they suggested that the adoption of environmental certification by organizations should be treated as a multistandard problem considering environmental sustainability, economy, and strategy [5].…”
Section: Literature Reviewmentioning
confidence: 99%
“…erefore, they suggested that the adoption of environmental certification by organizations should be treated as a multistandard problem considering environmental sustainability, economy, and strategy [5].…”
Section: Literature Reviewmentioning
confidence: 99%
“…These changes are costly for firms due to the certification process and the technological and organizational changes required [12,18]. In return, those firms that implement such practices can get comparative market advantages, such as improving their green image and enhancing the relationship with stakeholders, among other benefits [12,31]. VECs are expected to act as signaling devices for the society and, especially, for those consumers who are concerned about making more sustainable purchase decisions [32].…”
Section: Introductionmentioning
confidence: 99%
“…Being considered as a developing country by the International Monetary Fund (Brandao-Marques et al, 2020), it has a very active role in terms of environmental policy, especially in environmental education, climate change mitigation, ecotourism, and conservation (Blum, 2008;Flagg, 2018). The increasing role of environmental certifications and programs offers a channel for Costa Rican companies to improve their environmental and economic performance (André and Valenciano-Salazar, 2020;Birkenberg and Birner, 2018;Blackman and Naranjo, 2012;Blackman et al, 2014;Rivera, 2002).…”
mentioning
confidence: 99%